Those Who Made It - Tibbetts, John C. author. aut Link
XI, 235 p. 11 illus.
Keywords: What was it like to work behind the scenes, away from the spotlight's glare, in Hollywood's so-called Golden Age? The interviews in this book provide eye-witness accounts from the likes of Steven Spielberg and Terry Gilliam, to explore the creative decisions that have shaped some of Classical Hollywood's most-loved films.